La Teoria de A. Negri. Tra 'Pensare Nella' e 'Pensare Sulla' Congiuntura - Viparelli, Irene (2011)
The present article aims to reflect on the evolution of the theory of Negri, from the "Marxian" writings of the Sixties and Seventies, up to the last text, written in collaboration with M. Hardt, Commonwealth. Our hypothesis is that it is possible to take the logic of development of Negri's theory only by hypothesizing its belonging to the tradition of revolutionary thought; a tradition that is characterized by the intimate link between theoretical development and cyclical movement of capitalism. Using the Althusserian lexicon, we have defined this dynamic of development of revolutionary thought as alternating "thinking in" and "thinking about" conjuncture. The first part of the article is devoted to the analysis of the texts of the so-called "perishable worker": such texts, both for their subordination to the specific Italian conjuncture of the sixties and to the international crisis of the seventies, and for their search for a political strategy adequate to the class struggle in this specific context, can only be considered as an emblematic expression of a "thinking in the conguination". In the second part we dealt with the theoretical production of Negri, from the writings of the eighties up to Multitude, showing how the fundamental objective is to bring "to the form of the concept" a series of theoretical intuitions developed during the "conjunctural reflection" . Finally, in the last part, we formulated the hypothesis that, with Commonwealth, a new "theoretical displacement" is accomplished: the financial crisis of 2008 requires Negri to abandon again the "abstract" ground of the theoretical reflection, to immerse oneself in the "concreteness" of conjunctural reflection, in order to define a revolutionary strategy adequate to the contemporary productive forces, to the biopolitical Multitude. Astratto Il presente articolo si propone di reflettere sull' evoluzione della teoria di Negri, dagli scritti "marxiani" degli anni Sessanta e Settanta, fino all´último testo, scrito in collaborazione con M. Hardt, Commonwealth. La nostra ipotese à che sia possibilecogliere la logica di sviluppo della teoria di Negri soltanto ipotizzando la sua apparteneza alla tradizione del pensiero rivoluzionario; una tradizione che si caratterizza per líntimo legame tra sviluppo teorico e movimento ciclico del capitalismo. Utilizzando il lessico althusseriano, abbiamo definito tale dinamica di svilluppo del pensiero rivoluzionario come alternarsi "pensare nella" e del "pensare sulla" congiuntura. La prima parte dell´articolo è consacrata all´analisi dei testi del cosiddetto "perioso operaista": tali testi, sia per la loro subordinazione alla specifica congiuntura italiano degli anni sessanta e alla crisi internazionale degli anni settanta, sia per la loro ricerca di una strategia politica adeguata alla lotta di classe in questo specifico contesto, non possono che essere considerati come espressione emblematica di un "pensare nella" conguintura. Nella seconda parte ci siamo occupati della produzione teorica di Negri, dagli scritti degli anni Ottanta fino a Multitude, mostrando come l'obiettivo fondamentale sia quello di portare "alla forma del concetto" una serie di intuizioni teoriche sviluppate nel corso della "riflessione congiunturale". Infine, nell'ultima parte, abbiamo formulato l'ipotesi che, con Commonwealth, si compia un nuovo "dislocamento teorico": la crisi finanziaria del 2008 impone a Negri di abbandonare nuovamente l'"astratto" terreno della riflessionare teorica, per immergersi nella "concretezza" della riflessione congiunturale, al fine di definire una strategia rivoluzionaria adeguata alle forze produttive contemporanee, alla Moltitudine biopolitica. Resumo O presente artigo pretende refletir sobre a evolução da teoria de Negri, desde os escritos "marxianos" dos anos sessenta e setenta, até o último texto, escrito em colaboração com M. Hardt, Commonwealth. A nossa hipótese é a de que é possível tomar a lógica do desenvolvimento da teoria de Negri apenas pela hipótese de pertencer à tradição do pensamento revolucionário; uma tradição que é caracterizada pelo vínculo íntimo entre desenvolvimento teórico e movimento cíclico do capitalismo. Usando o léxico althusseriano, definimos essa dinâmica de desenvolvimento do pensamento revolucionário como uma alternância entre "pensar em" e "pensar sobre" a conjuntura. A primeira parte do artigo é dedicada à análise dos textos do chamado "trabalhador perecível": tais textos, tanto pela sua subordinação à específica conjuntura italiana dos anos sessenta como pela crise internacional dos anos setenta, e sua procura por uma estratégia política adequada à luta de classes nesse contexto específico, só pode ser considerada como uma expressão emblemática de um "pensar na conivência". Na segunda parte, tratamos da produção teórica de Negri, dos escritos dos anos oitenta, mostrando como o objetivo fundamental é trazer "à forma do conceito" uma série de intuições teóricas desenvolvidas durante a "reflexão conjuntural". Finalmente, na última parte, formulamos a hipótese de que, com a Commonwealth, um novo "deslocamento teórico" é realizado: a crise financeira de 2008 exige que Negri abandone novamente o fundamento "abstrato" da reflexão teórica, para imergir na "concretude" da reflexão conjuntural, para definir uma estratégia revolucionária adequada às forças produtivas contemporâneas, à Multitude biopolítica.